(untitled) (Global Journal of Medical Research, 2017)
An observational study was conducted on 650 Japanese quail chicks from hatching up to marketing age (0-6 wks) in a farm at Moij-jartack, Chittagong in Bangladesh to evaluate their management, growth and productive performance under litter floor rearing system. The total study period was 70 days. The chicks were hatched in the own hatchery farm where the hatchability rate was 71.42%. The daily amount of supplied ration was fixed and varied in different ages. The birds were reared for 6 wks (marketing age) and were sold when 120-130 gm weight was achieved. The feed conversion ratio (FCR) in 1 st wk was 1.4, but from (2-6) wks it was increased to 3.1, 5.24, 5.6, 5.6 and 6.37 respectively. The average weight was 130 gms at 6 wks with an average feed conversion ratio of 4.55: 1. Mortality rate decreased with age (2.42%). The farming was also profitable in terms of production per birds. It may be inferred that Japanese quail performs well under litter floor rearing in Bangladesh.